2006
DOI: 10.1038/sj.ki.5000007
|View full text |Cite
|
Sign up to set email alerts
|

Hemodialysis reduces inhibitory effect of plasma ultrafiltrate on LDL oxidation and subsequent endothelial reactions

Abstract: Oxidative modification of low-density lipoprotein (LDL) and its deleterious effect on endothelium is implicated in the pathogenesis of atherosclerosis. Endothelium responds to such an insult by upregulating the synthesis of heme oxygenase-1 (HO-1) and ferritin. Endothelial cell damage and dysfunction have been observed in patients with chronic kidney disease (CKD) on maintenance hemodialysis (HD). We studied the effect of low-molecular-weight components of uremic plasma on LDL oxidation and LDL-oxidation-provo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
1
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 48 publications
2
19
1
1
Order By: Relevance
“…The health effects of free p-Cresol and its conjugates have been inconsistent in previous studies [48, 49]. Here we found that increased level of plasma PCS was associated with longer LTL, suggesting a protective effect on biological aging.…”
Section: Discussioncontrasting
confidence: 40%
“…The health effects of free p-Cresol and its conjugates have been inconsistent in previous studies [48, 49]. Here we found that increased level of plasma PCS was associated with longer LTL, suggesting a protective effect on biological aging.…”
Section: Discussioncontrasting
confidence: 40%
“…The importance of this regulation is evidenced in the Hmox1 −/− mice that exhibit exaggerated injury under similar conditions and likely reflect an inability to modulate inflammation and subsequent repair processes. 93;127-129 Indeed animals lacking HO-1 show elevated mean arterial pressures basally. 130 In contrast, in mice in which HO-1 was selectively over-expressed in the heart, there is improved cardiac function, a reduced number of myocardial infarctions, and an overall reduction in inflammatory and oxidative injury after coronary artery ligation and reperfusion.…”
Section: Ho-1 and Cardiovascular Protectionmentioning
confidence: 98%
“…They are reactive species toward oxidation, thus considered to have antioxidant activity. Ujhelyi et al (18) have previously suggested that the decreased antioxidant capacity of plasma ultrafiltrate observed after a hemodialysis session is related to the removal of several protein-bound uremic toxins, including p -cresol. This indicates that phenolic uremic toxins, usually retained in patients with CKD, might have antioxidant activity.…”
Section: Discussionmentioning
confidence: 99%